Developing smart dumbbells based on iNEMO inertial measurement unit – B - Wu, Haozhou. (2013)
Over the past decades, Inertial Measurement Unit (IMU) has been widely applied in many areas including flight dynamics, entertainment, health care etc. Generally there are three sensors built in the unit i.e. accelerometer, which measures the linear acceleration including the gravity of the object; magnetometer, which detects the magnetic field in the vicinity, and gyroscope, which tells the angular velocity when the object rotates. Furthermore, with sensor fusion technology which merges all the raw data, more valuable information is available such as the spatial orientation and linear acceleration.